The Conversion of Senator Arthur H. Vandenberg : From Isolation to International Engagement - Kaplan, Lawrence S. (Book collections on Project MUSE., 2015)
This work argues for the importance of Arthur H. Vandenberg's role in America's conversion to a new status in the world, placing Vandenberg's name alongside other influential figures such as George Kennan, Dean Acheson, and John Foster Dulles. Vandenberg was a public man, well aware of his importance to his community, party, and nation. As co-secretary of state, he played a major role in bringing the Republican Party into a bipartisan relationship with the Truman administration. As chairman of the Senate Foreign Relations Committee in 1947 and 1948 and as ranking Republican on that committee in 1949, Vandenberg was arguably the key factor in moving the nation from its isolationist past to an internationalist future.